Dielectric characterization of meat using enhanced coupled ring-resonator - Taha Jilani, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
In this paper an enhanced coupled microstrip ring-resonator is presented for poultry meat quality evaluation. The proposed 1 GHz ring-resonator demonstrates significant change in resonance frequency while characterizing the meat with different moisture content. Measured and simulated results are in very good agreement where the maximum discrepancy observed is 4.24. Â© 2014 IEEE.